Social Construction of Body Positivity Movement on Instagram among Teenage Girls in Surabaya, Indonesia - Kiptiyah, Pipit Siti; Ridwan, Ahmad (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2025)
Body image on digital platforms, particularly Instagram, has become a significant arena for negotiating and redefining ideals of beauty, self-esteem, and identity, reflecting broader social shifts. This research examines the social construction of the body positivity movement on Instagram among teenage girls in Surabaya through Peter L. Berger’s theoretical framework, which posits that social reality is formed through externalization, objectivation, and internalization, where individuals and society co-create meanings through interaction. Employing a qualitative descriptive approach, this study involved 12 female informants aged 13-21 who actively use Instagram. Data were obtained through in-depth interviews and visual content analysis, and were then analyzed thematically to identify patterns in body image narratives, self-acceptance, and digital resistance. Findings reveal that these young women are not passive recipients of beauty norms; instead, they actively reconstruct bodily meanings through their everyday media practices. The body positivity movement emerges as a counter-narrative that transforms collective identity and redefines women’s bodies from objects to dignified subjects. This research contributes to media and body sociology, emphasizing critical digital literacy and inclusive education in fostering youth empowerment and gender-sensitive interventions.